Expression of Fas antigen and Fas ligand in bronchoalveolar lavage from silicosis patients - Agnès Hamzaoui; Jamel Ammar; Hédia Graïri; Kamel Hamzaoui (Hindawi Limited, 2003)
Objective: To understand the role of apoptosis through Fas/Fas ligand (FasL) interaction in the pathogenesis of silicosis, we examined the expression of Fas antigen, FasL and apoptosis in bronchoalveolar lavage fluid lymphocytes obtained from patients with silicosis.